FAKTOR-FAKTOR PENENTU KUALITAS JASA PERBANKAN (KAJIAN DARI PERSPEKTIF GENDER DAN POSISI PEKERJAAN PADA KARYAWAN BANK SURABAYA) - Magdalena Francisca Toar; Tatik Suryani (STIE Perbanas Surabaya, 2011)
Banks need to review what kind of service quality is expected by the customers. Before determinethe service quality strategy, it is necessary to synchronize the bank perception whichis represented by the perception of frontline and back-office employees, and customers toavoid gaps. The objectives of this study are such as (1) to examine the factors that determinethe service quality from perspective bank employee based on their position in frontline andback-office, and (2) to verify the perceptions differences on service quality based on gender.By judgmental and purposive sampling, this research gained 100 employees of banks in Surabayacity. Data were collected by questionnaire method. By using factor analysis and independentsample test, this research found that there are seven determinants of banking servicequality that are perceived by the employees and no differences in the perceptions of thedeterminants of service quality between frontline and back-office employees, neither on genderbased